Effectiveness of Phosphorus and Nitrogen Removal in the Water Treatment Process at Khmer Beverages, Phnom Penh - Mardy Serey; Sreypov Chhorn; Chinda Chhe (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: The aim of this study is to understand the process of water treatment in each step and to understand the effectiveness of the removal of phosphorus and nitrogen from wastewater. Methodology: For nitrogen removal must be through many processes such as Nitrogen fixation, or Ammonification, and Denitrification. For the phosphorus. The additional Ferric Chloride in the Aeration tanks to a reaction between the melt and the mud bolts is separated at the Clarifier tank. The Coagulation basin adds Ferric Chloride at 40% concentration of 0.05ml in contaminated water 1000ml for nitrogen and phosphorus concentration tests and studied in the condition the nitrogen can be removed from contaminated water well depending on the pH value and temperature. The removal of phosphorus by adding 0.05ml ferric chloride and 5ml of polymer cation 1040 (powder) can tank up to 80% phosphorus at the temperature of 200C and pH 7. Main Findings: As a result, the good conditions for nitrification are the pH of between 7.5 and 8.6 at temperature in the tank between 200C and 250C and the denitrification has a pH of between 7.5 and 8 and temperature in the tank from 200C to 350C. Result show that the remaining phosphorus is below the ministry of environment standard set (P <2mg/l). Novelty/Originality of this study: The next study should observe the amount of polymer to be applied after adding iron and studying the speed of iron chips as it affects the removal of phosphorus.